Non‐contrast enhanced simultaneous 3D whole‐heart bright‐blood pulmonary veins visualization and black‐blood quantification of atrial wall thickness - Ginami, Giulia (Magn Reson Med, 2018)
PURPOSE: Pre‐interventional assessment of atrial wall thickness (AWT) and of subject‐specific variations in the anatomy of the pulmonary veins may affect the success rate of RF ablation procedures for the treatment of atrial fibrillation (AF). This study introduces a novel non‐contrast enhanced 3D whole‐heart sequence providing simultaneous information on the cardiac anatomy—including both the arterial and the venous system—(bright‐blood volume) and AWT (black‐blood volume). METHODS: The proposed MT‐prepared bright‐blood and black‐blood phase sensitive inversion recovery (PSIR) BOOST framework acquires 2 differently weighted bright‐blood volumes in an interleaved fashion. The 2 data sets are then combined in a PSIR‐like reconstruction to obtain a complementary black‐blood volume for atrial wall visualization. Image‐based navigation and non‐rigid respiratory motion correction are exploited for 100% scan efficiency and predictable acquisition time. The proposed approach was evaluated in 11 healthy subjects and 4 patients with AF scheduled for RF ablation. RESULTS: Improved depiction of the cardiac venous system was obtained in comparison to a T(2)‐prepared BOOST implementation, and quantified AWT was shown to be in good agreement with previously reported measurements obtained in healthy subjects (right atrium AWT: 2.54 ± 0.87 mm, left atrium AWT: 2.51 ± 0.61 mm). Feasibility for MT‐prepared BOOST acquisitions in patients with AF was demonstrated. CONCLUSION: The proposed motion‐corrected MT‐prepared BOOST sequence provides simultaneous non‐contrast pulmonary vein depiction as well as black‐blood visualization of atrial walls. The proposed sequence has a large spectrum of potential clinical applications and further validation in patients is warranted.